2022
DOI: 10.1002/jor.25352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hindlimb suspension on development of proximal and distal femur morphological abnormalities in growing rats

Abstract: Although morphological abnormalities of the femur are known predisposing factors for numerous musculoskeletal disorders, the etiology of these abnormalities is poorly understood. This study aimed to investigate whether femoral morphogenesis is affected by hindlimb suspension (HS) in growing rats. We used 41 four‐week‐old female rats in this study. In the HS groups, rats were suspended from their tails for 2, 4, and 8 weeks. Age‐matched animals were used as controls. We examined morphological indices of the fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…A previous study demonstrated that the effect of unloading on the formation of femur morphologies was associated with numerous musculoskeletal disorders, including patellar instability and dislocation. 9 This is the first report to provide the evidence that reduced mechanical stress on joints during the growth phase may be an Data indicate the number of knee joints that were positive for each parameter divided by the total number of knees (upper) and incidence rate (lower).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A previous study demonstrated that the effect of unloading on the formation of femur morphologies was associated with numerous musculoskeletal disorders, including patellar instability and dislocation. 9 This is the first report to provide the evidence that reduced mechanical stress on joints during the growth phase may be an Data indicate the number of knee joints that were positive for each parameter divided by the total number of knees (upper) and incidence rate (lower).…”
Section: Discussionmentioning
confidence: 93%
“…In the HS groups, HS was performed for 2, 4, or 8 weeks as previously described with slight modifications. 9 Briefly, rats aged 4 weeks in both groups were anesthetized via intraperitoneal injection of ketamine (60 mg/kg) and xylazine (8 mg/kg). In the HS groups, a Kirschner wire was transversely inserted into the rat tail.…”
Section: Hindlimb Suspensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the 7 μm voxel size that we used may not be sufficient resolution to observe the presence of thin trabeculae, at which point, nanoCT may be required to visualize changes. However, trabecular bone is important for transmitting forces throughout the anatomy of the bone, and so it would logically decrease in the context of disuse, but not aging [34,35].…”
Section: Discussionmentioning
confidence: 99%